2016
DOI: 10.1038/srep36911
|View full text |Cite
|
Sign up to set email alerts
|

Electronic bonding analyses and mechanical strengths of incompressible tetragonal transition metal dinitrides TMN2 (TM = Ti, Zr, and Hf)

Abstract: Motivated by recent successful synthesis of transition metal dinitride TiN2, the electronic structure and mechanical properties of the discovered TiN2 and other two family members (ZrN2 and HfN2) have been thus fully investigated by using first-principles calculations to explore the possibilities and provide guidance for future experimental efforts. The incompressible nature of these tetragonal TMN2 (TM = Ti, Zr, and Hf) compounds has been demonstrated by the calculated elastic moduli, originating from the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…To date, VN 2 , ZrN 2 and HfN 2 have not been synthesized. In a previous theoretical study, 23 ZrN 2 and HfN 2 are assumed to have the same ground state structure as TiN 2 since the three TMs are in the same group in the periodic table. Our structure search confirmed this conjecture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, VN 2 , ZrN 2 and HfN 2 have not been synthesized. In a previous theoretical study, 23 ZrN 2 and HfN 2 are assumed to have the same ground state structure as TiN 2 since the three TMs are in the same group in the periodic table. Our structure search confirmed this conjecture.…”
Section: Resultsmentioning
confidence: 99%
“… 7 In addition to the realized pernitrides, many others were predicted to exist as well, await for future synthesis. The long list includes ZrN 2 , 20 CrN 2 , 21 NbN 2 , 22 HfN 2 , 23 WN 2 , 24 and others. 25–27 Several new prototypic structures were proposed for TM pernitrides, including the pyrite-type, P 6 3 / mmc and P 6̄ m 2 structures, some of which were suggested based on the structure analogy with chemically similar materials.…”
Section: Introductionmentioning
confidence: 99%
“…For 3D materials, Table 2 lists the calculated ideal tensile and shear strengths via affine pure deformation of a broad class of materials with different symmetry except triclinic system, together with the previous theoretical values [4,7,27,[49][50][51][52][53] for comparison. It is found that all calculated values by ADAIS code are in reasonable agreement with the previous theoretical values [4,7,27,[49][50][51][52][53], confirming the validity of ADAIS code for 3D materials. Also, Table 3 lists the calculated uniaxial and biaxial tensile strengths of 2D materials with hexagonal and rectangular systems, together with the previous theoretical values [23,54] for comparison.…”
Section: Ideal Tensile and Shear Strengths By Affine Deformationmentioning
confidence: 99%
“…According to the symmetry of crystal, the number of independent elastic constants can be reduced. ZrN 2 and HfN 2 are of tetragonal symmetry, and thus have six independent elastic constants and the elastic stiffness tensor matrix can be expressed in the following way [19]:…”
Section: Elastic Propertiesmentioning
confidence: 99%